Design of e-Marketplace for Village-owned Small, Micro and Medium Enterprise using Rapid Application Development - Sutrisno, Agung; Andreswari, Rachmadita; Ambarsari, Nia; Syahrina, Alvi; Puspitasari, Warih; Novianti, Atik; Darmawan, Irfan (International Journal of Innovation in Enterprise System, 2020)
Village-Owned Enterprises (BUM Desa) Pakis Sabilulungan is a business entity that houses small, micro and medium-sized businesses located in Mekarsari Village, Pasirjambu, Bandung, Indonesia. At present, BUM Desa Pakis has begun to pioneer several businesses including the production of snacks, coffee, crafts, and clothing. But there are obstacles where marketing is still limited to one sub-district and income tends to stagnate. Therefore, we need an internet-based technology that is able to help marketing more broadly and more easily than the current situation. The proposed technology in BUM Desa Pakis is a web-based e-marketplace, where all business owners can sell goods on the same platform. In its development, the prototyping method was used. This is because BUM Desa needs a description of the application that will be used before further development. The results of the e-Marketplace development on BUM Desa show that the marketing process can be carried out faster, payments can be made through bank transfers and delivery can be done through expeditions. This is significantly able to expand product marketing from Mekarsari Village